Cross-border Downstream Benefit Sharing in Reservoir Type Hydropower Projects: Case of Budhi Gandaki Storage Project in Nepal - Upadhyay, Surya Nath; Gaudel, Prakash (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
This paper analyses the role of the principle of downstream benefit sharing under international water law regime in the management of cross-border water courses. This paper argues that the principle of downstream benefit sharing may play a key role in wiping away the long-existing distrust between countries as well as hold the potential to usher in a new phase of cooperation between riparian neighboring countries, such as Nepal and India. If pursued in good faith the downstream benefit principle would enjoin erstwhile losers of the vast potential to a cooperative mechanism where they could find themselves in a win-win situation. The Budhi Gandaki Storage Project presents a unique opportunity for employing this new paradigm of cooperation between two countries: Nepal and India. In this paper, we present the example of India that is facing a water and energy crisis for which it may ease to a considerable extent its problem by depending on Nepal for these resources. Downstream benefit sharing may provide India an opportunity to gain the confidence of the Nepalese people for developing many hydro projects with or without water augmentation resulting into multiple benefits downstream in India. Employing the downstream benefit sharing principle might requirere visiting treaties like Gandak Project Agreement. DOI: http://dx.doi.org/10.3126/hn.v14i0.11267 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014, January Page: 59-64